Directions of Development of Tourism in the Polish-Ukrainian Cross-Border Area in the New European Union Programming Period (2014–2020) in the Context of Regional Planning Documents - Andrzej Miszczuk (Barometr Regionalny)
The objective of the article is to present the state and directions of the development of tourism in the Polish-Ukrainian cross-border area covering the Lubelskie and Podkarpackie voivodships and the Lviv and Volyn Oblasts in the context of regional strategic documents prepared in the scope of the new EU perspective for the years 2014–2020. In spite of the lack of a uniform strategic document for the purposes of development of the entire cross-border area in the years 2014–2020, the area is considered in development strategies of Polish voivodships and in related documents. In the case of the Lubelskie Voivodship, it is the cross-border cooperation strategy, and in the case of the Podkarpackie Voivodship — subregional strategic programmes. All of these documents consider tourism, including the specification of the objectives, priorities, and directions of activities, and even proposed projects. The content of these documents can provide a good basis for the development of modern tourism products at the local, regional, and cross-border level, with a potential to stimulate tourist traffic in the cross-border area. Possible support from the EU resources in the new financial perspective 2014–2020 is important for these types of activities.